Structural investigations of annealed ZnS:Cu, Ga film phosphors - Lytvyn, O.S.; Khomchenko, V.S.; Kryshtab, T.G.; Lytvyn, P.M.; Mazin, M.O.; Prokopenko, I.V.; Rodionov, V.Ye.; Tzyrkunov, Yu.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
X-ray and atomic force microscopy techniques were used for investigations of crystalline structure and nano-morphology of ZnS:Cu thin films. The films were deposited by electron beam evaporation on substrates of various types (glass, BaTiO₃, silicon). New non-vacuum method of annealing was applied for improvement electro-physical parameters of ZnS:Cu based thin film electroluminescent devices. The annealing was carried out at the temperature of 850 °C. Ga co-doping was applied for the same structures in the course of the annealing process. It was shown that recrystallization process at annealing leads to improvement of ZnS:Cu films structural perfection without changes of crystal structure. This improvement provides tenfold increase of photo- and electroluminescence brightness and decrease of threshold voltage down to 10 V, as well as enhancement of device stability against degradation.